RANCANGAN MODIFIKASI ALAT PENARIK BETA SISTEM PROPELLER HARTZELL TIPE HC-E4N-3G SERIES DI BALAI BESAR KALIBRASI FASILITAS PENERBANGAN - M. Ichwan Ridhani; Ego Widoro; M. Subiat Wiranata Kusuma (Politeknik Penerbangan Indonesia Curug, 2018)
The removal of HC-E4N-3G type Hartzell propellers at the King Air 200 aircraft own Balai Besar Kalibrasi Fasilitas Penerbangan (BBKFP) is carried out on scheduled and unscheduled maintenance. When removal and installation this propellers using available tools, technicians often have difficulty because requiring large power and unsafe conditions when withdrawing the propeller beta system due to the design of the tool, such need withdrawing tool modifications of HC- E4N-3G type hartzell propeller beta system. Theories relating to modification of this tool include maintenance, hartzell propeller type HC-E4N-3G Series, material selection, load, circle shape, torque, stress, security factor and thread theory. The design of this tool modification is divided into several parts such as puller rod, threaded pressing rod, threaded retaining body, rotating arm and pressing threaded cylinder. Based on the calculation and analysis process all parts of the withdrawing tool are made from S45C material and tool modification with dimensions of all parts according to the calculation and analysis process successfully able to draw HC- E4N-3G type hartzell propeller beta system beta Hartzell propeller